Aberration corrections for non‐Bragg–Brentano diffraction geometries. Issue 1 (31st January 2017) - Rowles, Matthew R.; Buckley, Craig E.
Abstract : A variety of physically meaningful geometrical and preferred orientation corrections are derived and summarized. The application of these corrections allows for realistic modelling based on the fundamental parameters approach to be undertaken. Abstract : The construction of peak intensity, profile and displacement aberration functions based on the geometry of a powder diffraction measurement allows for physically realistic corrections to be applied in Rietveld modelling through a fundamental parameters approach. Parallel‐beam corrections for asymmetric reflection and Debye–Scherrer geometry are summarized, and corrections for thin‐plate transmission are derived and validated. Geometrically correct implementations of preferred orientation models are also summarized.